347 Clinical outcomes of ovarian cancer patients treated with ALKS 4230, a novel engineered cytokine, in combination with pembrolizumab: ARTISTRY-1 trial. (10th December 2020) - Winer, Ira; Gilbert, Lucy; Vaishampayan, Ulka; Rosen, Seth; Hoimes, Christopher; Muzaffar, Jameel; Spreafico, Anna; McDermott, David; Chu, Quincy; Dumas, Olivier; Chauhan, Aman; Chaudhry, Arvind; et al.
Abstract : Background: ALKS 4230 is a novel engineered cytokine that selectively targets the intermediate-affinity interleukin-2 receptor complex to activate CD8+ T cells and natural killer cells. 1 The ARTISTRY-1 trial (NCT02799095 ) has shown encouraging efficacy and acceptable tolerability of ALKS 4230 among patients with advanced solid tumors. 2 We report a detailed analysis of ovarian cancer (OC) patients who received combination therapy in ARTISTRY-1. Methods: ARTISTRY-1 is an ongoing multicohort phase 1/2 trial exploring intravenous ALKS 4230 as monotherapy and combined with pembrolizumab. OC patients were enrolled into a cohort with mixed anti PD 1/L1 unapproved tumor types who had progressed on prior chemotherapy. OC patients received ALKS 4230 (3 µg/kg) on days 1–5 and pembrolizumab (200 mg) on day 1 of a 21 day cycle. Outcomes presented include antitumor activity (RECIST v1.1) and safety as of 7/24/2020. To evaluate changes in tumor microenvironment (TME), baseline and on-treatment biopsies were collected. Results: Fourteen heavily pretreated patients with OC were enrolled. Patients received a median of 5 (range, 2 11) prior regimens and all were previously treated with platinum based therapy. Among 13 evaluable patients with ≥1 assessment, 9 experienced disease control and 4 experienced disease progression; median treatment duration was approximately 7 weeks. Three patients experienced an objective response, including 1 complete response, 1 partial response (PR), and 1 unconfirmed PR; all were platinum resistant and negative for BRCA mutations. Five patients experienced tumor burden reductions (table 1 ). Treatment-related adverse events at the doses tested have generally been transient and manageable, with the majority being grade 1 and 2 in severity. Overall, based on preliminary data, the combination with ALKS 4230 did not demonstrate any additive toxicity to that already established with pembrolizumab alone. Additional safety and efficacy data are being collected in ongoing cohorts. In the monotherapy dose escalation portion of the study, ALKS 4230 alone increased markers of lymphocyte infiltration in 1 paired melanoma biopsy (1 of 1; on treatment at cycle 2); CD8+ T cell density and PD-L1 tumor proportion score increased 5.2- and 11 fold, respectively, supporting evidence that ALKS 4230 has immunostimulatory impact on the TME and providing rationale for combining ALKS 4230 with pembrolizumab (figure 1 ). Conclusions: The combination of ALKS 4230, an investigational agent, and pembrolizumab demonstrates an acceptable safety profile and provides some evidence of tumor shrinkage and disease stabilization in some patients with heavily pretreated OC. This regimen could represent a new therapeutic option for these patients. Acknowledgements: The authors would like to thank all of the patients who are participating in this trial and their families. The trial is sponsored by Alkermes, Inc. Medical writing and editorial support was provided by Parexel and funded by Alkermes, Inc. Trial Registration: ClinicalTrials. gov NCT02799095 Ethics Approval: This trial was approved by Ethics and Institutional Review Boards (IRBs) at all trial sites; IRB reference numbers 16–229 (Dana-Farber Cancer Institute), MOD00003422/PH285316 (Roswell Park Comprehensive Cancer Center), 20160175 (Western IRB), i15-01394_MOD23 (New York University School of Medicine), TRIAL20190090 (Cleveland Clinic), and 0000097 (ADVARRA). References: Lopes JE, Fisher JL, Flick HL, Wang C, Sun L, Ernstoff MS, et al. ALKS 4230: a novel engineered IL-2 fusion protein with an improved cellular selectivity profile for cancer immunotherapy. J Immunother Cancer 2020;8:e000673. doi: 10.1136/jitc-2020-000673. Vaishampayan UN, Muzaffar J, Velcheti V, Winer I, Hoimes CJ, Rosen SD, et al. ALKS 4230 monotherapy and in combination with pembrolizumab (pembro) in patients (pts) with refractory solid tumors (ARTISTRY-1). Oral presentation at: European Society for Medical Oncology Annual Meeting; September 2020; virtual.